Controlled deposition of Pd and in on carbon fibers by sequential electroless plating for the catalytic reduction of nitrate in water - Miranda Zoppas, Fernanda (2016)
Catalysts containing 1.8 wt.% of Pd and different In loadings were prepared by sequential electroless plating on activated carbon felts (ACF). Homogeneous structures were obtained, with In particles deposited at the top of a tiny Pd film. The catalyst with the higher In loading (Pd:In ratio of 2.0) presented high activity and good selectivity towards nitrogen, with negligible deactivation after 6 h of time-on-stream and three consecutive nitrate pulses. Besides the promising catalytic behavior, PdIn/ACF have the advantages of an open structure, which is highly accessible to the reactants, with no need of separation after the reaction.